• 9-2x=5,5-7x

    4x-3,6=0

    5x-0,8=2x+16

    3x+2,7=0

    4-2(x+3)=4(x-5)

    2x+7=3x-2(3x-1

Ответы 1

  • 9-2x=5,5-7x-2х+7х=5,5-95х=-3,5х= -0,74x-3,6=04х=3,6х=0,85x-0,8=2x+165х-2х=16+0,83х=16,8х=5,63x+2,7=03х=-2,7х= -0,94-2(x+3)=4(x-5)4-2х-6=4х-20-2х-4х=-20-4+6-6х= -18х=32x+7=3x-2(3x-1)2х+7=3х-6х+12х-3х+6х=1-75х=-6х=-1,2
    • Автор:

      jonahwebb
    • 5 лет назад
    • 0
  • Добавить свой ответ

Войти через Google

или

Забыли пароль?

У меня нет аккаунта, я хочу Зарегистрироваться

How much to ban the user?
1 hour 1 day 100 years